Investigating the Influence of Leaf Area Index (LAI) Variations of Green Facade on Built Wall Performance: A Study Using Energy Balance Model - Mitra, Sreemoyee; Das, Vinay Mohan (Calibrating Urban Livability in the Global South, 2024)
Increasing urbanization has indeed led to the deterioration of green spaces in cities, raising concerns about the environmental impact and quality of urban living. In response to these challenges, the concept of green façades has emerged as a promising solution, particularly in enhancing the energy efficiency of built structures and improved urban liveability alongside cost optimisation in tropical countries. This study aims to explore the thermal behaviour of opaque constructions when integrated with vegetation during high radiation phase, focusing on the geographical location of Delhi. The mathematical model proposed by Susorova is employed to investigate the impact of foliage and façade orientation on the inside surface temperature (Tin) of walls. The existing model cannot be used be for pre-installation analysis, thus the researcher has replaced the factor of outside surface temperature (To) with Sol-air temperature (Tsol-air) making it suitable through mathematical modelling for pre-installation analysis. The independent factors considered are leaf area index (LAI) and incoming radiation, as they significantly influence thermal performance. Specifically, the study reveals that the effect of LAI varies during direct and diffused radiation phases. For eastern and western façades, an LAI of 1 or 2 yields the most significant reduction in Tin during high radiation phases, whereas the northern façade benefits from an LAI of 4 due to its exposure to diffused radiation. The southern façade exhibits a similar pattern as western and eastern façades, but with minimal variation in temperature magnitude. Additionally, the study delves into the contribution of short-wave radiation, long-wave radiation, and convective heat/gain in the heat balance equation, studying their influence with varying LAI. The findings of this research provide valuable insights for designing green façades on vertical structures in similar climatic conditions to optimize passive cooling and overall energy efficiency, thereby enhancing urban liveability in densely populated areas.